SHIFTING NOIR ELEMENTS: AN OVERVIEW ON NOIR FICTION IN SOUTHEAST ASIA - Ririn Kurnia Trisnawati (Faculty of Humanities, Universitas Jenderal Soedirman, 2017)
The emergence of noir fiction in Southeast Asian countries has showcased particular evolvement of noir elements. The noir works produced in this region have embraced shifting noir themes and noir protagonists that slightly move away from what formerly constitutes noir fiction. Thus, this study aims at investigating to what extent these two noir elements from noir fiction produced in Southeast Asia has differed from its preceding noir works in the scholarship of noir genre. As a preliminary finding, this study only highlights the shifting noir elements taken from selected noir stories represented by some noir anthologies produced in Southeast Asia. They are KL Noir from Malaysia, Singapore Noir from Singapore, and Manila Noir from the Philippines. The result shows that noir themes have departed from criminality and violence to some other contextualized themes such as supernaturalism, religion, and colonial legacy. Meanwhile, noir protagonists are portrayed as those who are involved with criminality not only as criminals but also as ‘heroes’. Finally, what is discussed in this study is expected to contribute to a larger discussion of fluidity in noir genre, and, also, noir, or darkness, is proven to be derived from various perspectives.